The Effect of Additional Pineapple (Ananas comosus L. Merr.) Peel Pectin on the Characteristics of Coal Fly Ash Geopolymer - Nuni Widiarti; Nandia Salsa Restu Mulyani; Ella Kusumastuti; Ridho Prasetyo (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Fly ash-based geopolymer concrete is a candidate for a more sustainable material than concrete, with lower embodied energy and high early-age compressive strength properties. This work has focused on studying the use of pineapple peel pectin as an additive to enhance the compressive and split tensile strength achievable in a geopolymerization process. The compressive strength and split tensile strength were tested by physical testing, and the mineral phases, functional groups, and microstructure were analyzed by chemical analysis (XRD, FTIR, and SEM-EDX). Geopolymers containing 0%, 1%, and 2.5% pectin were fabricated. The surprising optimum was the 1% variation, which reached compressive strength of 22.13 MPa and split tensile strength of 3.18 MPa when making medium-quality concrete. XRD results of the best performing 1% sample exhibited mainly an amorphous phase, where amorphization is evident at 20–40°2θ due to broad signal peaks, a sign of successful geolypolimerization. Geopolymerization was also confirmed by FTIR analysis through the presence of Si–O–Si and Si–O–Al asymmetric stretching vibration peaks at 1018.41 cm−1, illustrating the inclusion of pectin observed by the C–H stretches in the range 2900–2300 cm−1 and the carboxyl group stretch at 1635.64 cm−1. The microstructure of the quality concrete 1% formulation was characterized by a tight, perfect structure as seen through SEM images, while the 0% and 2.5% mixes had more porous and cracked structures. These results suggest that 1% pectin incorporation improves geopolymer mechanical performance without adversely affecting structure, merits for further mechanical properties, and long-term stability.